Application and evaluation of industrial waste residue and bentonite for solidification and stabilization of sewage sludge - Anhui Wang; Xidong Zhang; Zhangqian Wu; Wei Duan; Shaoyun Pu (Scientific Reports)
Abstract This study examines the applications of industrial waste residue and bentonite in treating sewage sludge. An industrial waste residue-based composite binder (IWCB) was formulated by integrating ground granulated blast furnace slag, desulfurized gypsum, and Portland cement. The optimal formulation for IWCB and the suitable quantity of bentonite were thoroughly ascertained through unconfined compressive strength testing of the solidified sludge, accompanied by analyses of heavy metal concentrations and chemical oxygen demand in the leachate. The factors affecting the mechanical properties and environmental safety performance of the solidified sludge were also assessed. The microscopic characteristics and solidification mechanism of IWCB–bentonite-solidified sludge were further elucidated. The findings indicate that IWCB substantially outperformed Portland cement in enhancing the strength of sewage sludge. The inclusion of bentonite significantly improved the mechanical strength and environmental safety of IWCB-solidified sludge, with an optimal bentonite content of 10%. Moreover, the addition of bentonite refined the pore structure of the solidified sludge and, together with the IWCB, boosted the compactness and mechanical strength of the sludge. This amalgamation also enhanced the stabilization of heavy metals and organic matter within the solidified sludge. These conclusions give valuable insights into the low-carbon solidification and reclamation of sewage sludge.